1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Neuropeptide Tyrosine 13–36, a Y2 Receptor Agonist, as Determined by NMR

Abstract: The three-dimensional structure of neuropeptide tyrosine (NPY) 13 -36, a specific Y2 receptor agonist, has been investigated by two-dimensional 'H-NMR spectroscopy in solution. Analysis of the doublequantum-filtered correlation spectroscopy (DQFCOSY), total correlation spectroscopy (TOCSY) and nuclear Overhauser enhancement spectroscopy (NOESY) spectra provided a complete assignment of the proton signals. The interproton connectivities observed in the NOESY spectra comprised 166 intraresidue and 95 interresidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…[61] Other authors have investigated mutants of truncated or cyclized versions of NPY. [62][63][64][65][66] Keire et al also estimated from CD and NMR spectra the helical content of PYY and the highly Y2-subtype-specific PYY fragment PYY . [67] The calculated helicity for PYY is 42 % and for PYY(3-36) is only 23 %, a result showing that the removal of two N-terminal amino acids resulted in major conformational alterations in solution; this observation was confirmed by our own dynamics data on PYY(3-36) (see below).…”
Section: The Solution Structures Of Peptides From the Npy Familymentioning
confidence: 98%
“…[61] Other authors have investigated mutants of truncated or cyclized versions of NPY. [62][63][64][65][66] Keire et al also estimated from CD and NMR spectra the helical content of PYY and the highly Y2-subtype-specific PYY fragment PYY . [67] The calculated helicity for PYY is 42 % and for PYY(3-36) is only 23 %, a result showing that the removal of two N-terminal amino acids resulted in major conformational alterations in solution; this observation was confirmed by our own dynamics data on PYY(3-36) (see below).…”
Section: The Solution Structures Of Peptides From the Npy Familymentioning
confidence: 98%
“…The addition of TFE stabilized the helical structure throughout the molecule, as expected, although the structure was not as regular an R-helix in aqueous TFE as the unbridged analogue Ac[Leu 28,31 ]NPY [24][25][26][27][28][29][30][31][32][33][34][35][36] . 27 To stabilize the helical structure throughout the peptide in the absence of TFE would presumably require the introduction of an additional lactam bridge (possibly overlapping the 28/32 bridge) and/or an i to i + 7 covalent link.…”
Section: Discussionmentioning
confidence: 71%
“…Because we found a helical structure for Ac-cyclo 28/32 -[Ala 24 ,Lys 28 ,Leu 31 ,Glu 32 ]NPY [24][25][26][27][28][29][30][31][32][33][34][35][36] in aqueous TFE and Rist et al 33 described a hairpin structure for the closely related peptide Ac-cyclo 28/32 [Lys 28 ,Glu 32 ]NPY [25][26][27][28][29][30][31][32][33][34][35][36] , which differs from our peptide in lacking the N-terminal Ala and having Ile 31 in place of Leu 31 , a more detailed comparison was called for. We therefore determined the structures of these two peptides, as well as a third lactam-bridged peptide containing Ala 24 and Ile 31 , under solution conditions (30% aqueous TFE, pH 5.0, 308 K) essentially identical to those described by Rist et al 33 As shown in Figure 5, all three peptides adopt similar helical structures except for the N-terminus of peptide II, which is less well-ordered.…”
Section: Discussionmentioning
confidence: 98%
“…It might be speculated that ADAPT contains some other active compound(s) synergistically increasing the expression of NPY. Interestingly tyrosol, salidroside, and NPY contain five tyrosine residues (Labelle et al, 1997), and all have the same p -hydroxyl-methylene residue. The importance the tyrosine moieties for brain receptors binding and NPY activity has been demonstrated (Martel et al, 1990).…”
Section: Discussionmentioning
confidence: 99%